ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT DI DESA LARIANG KECAMATAN TIKKE RAYA KABUPATEN MAMUJU UTARA - Hastutik, Hastutik; Tangkesalu, Dance; Sulaeman, Sulaeman (AGROTEKBIS, 2019)
Lariang village is one of five villages in Tikke Raya sub-district of North Mamuju district, West Sulawesi province. This village was one of palm production centers in the Norh Mamuju district chosen as the research site.  The purpose of this research was to determine the income of Palm Oil farming during its 24 harvesting times for one year starting from July 2016 until June 2017 in Lariang village, Tikke Raya sub-district, North Mamuju district.  Thirty two respondents were selected from population of 151 farmers using a Random Sampling proportional method. Income analysis (Soekartawi, 2002) was used to analyze the data collected. The average land area size owned by every respondent was 2.17 ha. It was found that the total revenue resulted from the farming was IDR 44,274,193.5/ha.  With the total production cost of IDR 13.980.027,6/ha, the farmer was able to generate income of IDR 30,294,165.9/ha.